A Niebuhrian pacifism for an imperfect world. (June 2021) - Moses, Jeremy
This article considers the role that might be played by the political thought of Reinhold Niebuhr in contemporary debates over pacifism. It begins with an overview of Niebuhr's changing position on pacifism, showing how his early commitment to anti-war principles gradually faded over time and was replaced with a pragmatic approach to just war thinking in his later life. The article then considers whether this drift away from pacifism necessarily means that there is nothing in Niebuhrian Christian realism for contemporary pacifist thought. Drawing on Niebuhr's critique of perfectionist liberalism, it argues that an imperfect and non-absolute pacifism that accepts the permanent possibility of political violence but refuses to offer moral endorsement to such violence can offer a viable political position in current debates on war and peace, particularly in opposition to just war approaches.